1994
DOI: 10.1002/arch.940270203
|View full text |Cite
|
Sign up to set email alerts
|

Chitin synthesis in Spodoptera frugiperda wing imaginal discs. II. Selective action of chlorfluazuron on wheat germ agglutinin binding and cuticle ultrastructure

Abstract: The action of the chitin synthesis inhibitor, chlorfluazuron, was investigated in Spodoptera frugiperda wing imaginal discs cultured in vitro. Electron microscopy and cytochemical labeling with a lectin, wheat germ agglutinin (WGA), were used to monitor morphogenesis, as well as the presence and localization of chitin and non-polymerized N-acetyl-D-glucosamine (GlcNAc). Chlorfluazuron (CFA) selectively inhibited 20-hydroxyecdysone-stimulated chitin synthesis and procuticle deposition in imaginal discs, without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
2
3
0
Order By: Relevance
“…In the present experiments, the ratio of cellular GlcNAc level and protein contents in Tn5B1-4 and Sf-21 cells was significantly decreased as the concentration of chlorfluazuron increased. This result is consistent with previous reports that the nonpolymerized GlcNAc in the extracellular matrix was present in both chlorfluazuron-treated and control Spodoptera frugiperda SFD1 cells, and the accumulation of N-acetyl-D-glucosamine-rich glycopeptides in Plodia interpunctella IAL-PID2 cells could be prevented by the use of teflubenzuron [31,32]. However, GlcNAc was not detected in both Hek293 and HepG2 cells; this may indicate that the selective toxicity of chlorfluazuron to lepidopteran cells is related to effects on the GlcNAc pathway.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present experiments, the ratio of cellular GlcNAc level and protein contents in Tn5B1-4 and Sf-21 cells was significantly decreased as the concentration of chlorfluazuron increased. This result is consistent with previous reports that the nonpolymerized GlcNAc in the extracellular matrix was present in both chlorfluazuron-treated and control Spodoptera frugiperda SFD1 cells, and the accumulation of N-acetyl-D-glucosamine-rich glycopeptides in Plodia interpunctella IAL-PID2 cells could be prevented by the use of teflubenzuron [31,32]. However, GlcNAc was not detected in both Hek293 and HepG2 cells; this may indicate that the selective toxicity of chlorfluazuron to lepidopteran cells is related to effects on the GlcNAc pathway.…”
Section: Discussionsupporting
confidence: 93%
“…The growth of animal cells releases more carbon dioxide and/or acidic materials into the culture medium [28,29]. This result is consistent with previous reports that the nonpolymerized GlcNAc in the extracellular matrix was present in both chlorfluazuron-treated and control Spodoptera frugiperda SFD1 cells, and the accumulation of N-acetyl-D-glucosamine-rich glycopeptides in Plodia interpunctella IAL-PID2 cells could be prevented by the use of teflubenzuron [31,32]. In the present experiments, the ratio of cellular GlcNAc level and protein contents in Tn5B1-4 and Sf-21 cells was significantly decreased as the concentration of chlorfluazuron increased.…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, the changes in these enzyme activities ultimately lead to deformations or mortality of treated larvae. These results were supported by those of Zimowska et al, 1994;Oberlander and Silhacek 1998;Palli and Retnakaran 1999;Oberlander and Samagghe 2001 who found that the mode of action of the BPUs; chlorfluazuron, diflubenzuron and teflubenzuron were include inhibition of chitin synthesis due to an inhibition of the protease enzyme that activates chitin synthase as well as activation of chitinase and phenoloxidase, which are both connected with chitin catabolism.…”
Section: Discussionmentioning
confidence: 58%
“…If the active site of the CS faces the inner side of the vesicle, such a hypothesis is questionable, as one must consider a special penetration mechanism for the relatively large substrate molecule into the chitosomal vesicle. Moreover, the size of the vesicle is too small to accommodate very large chitin polymers 9. Insertion of CS into plasma membranes, be it as individual molecules or via association with chitosomal vesicles, involves the mediation of targeting and recognition proteins.…”
Section: Chitin Formationmentioning
confidence: 99%